2011
DOI: 10.5664/jcsm.1068
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sleep Apnea, Fat Distribution, and Insulin Resistance in Obese Children

Abstract: Background:Obstructive sleep apnea (OSA) is associated with obesity, inflammation, and insulin resistance. The role of fat distribution in OSA pathogenesis has not been established in children. The objective of the study is to examine the relationship between fat distribution, OSA, and insulin resistance in an unselected population of obese children. Methods: All obese (BMI > 95th percentile) children (ages 5-18 y) seen at a pediatric obesity clinic were invited to participate. Subjects underwent polysomnograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 39 publications
6
57
0
2
Order By: Relevance
“…In a community-based study of predominantly postpubertal adolescents, strong associations were demonstrated between OSA and the metabolic syndrome, as well as with individual metabolic parameters, such as fasting insulin and homeostatic model assessment (HOMA) 29,84,85. Sleep fragmentation and intermittent hypoxia were also found to be associated with decreased insulin sensitivity in obese adolescent boys 86.…”
Section: Morbidity Of Osamentioning
confidence: 99%
See 1 more Smart Citation
“…In a community-based study of predominantly postpubertal adolescents, strong associations were demonstrated between OSA and the metabolic syndrome, as well as with individual metabolic parameters, such as fasting insulin and homeostatic model assessment (HOMA) 29,84,85. Sleep fragmentation and intermittent hypoxia were also found to be associated with decreased insulin sensitivity in obese adolescent boys 86.…”
Section: Morbidity Of Osamentioning
confidence: 99%
“…Fatty infiltrates within the compartments of the upper airway structures and the neck are likely to result in upper airway narrowing and increased pharyngeal collapsibility. Central obesity also reduces the functional residual capacity of the lungs, due to abdominal visceral fat impinging on the chest cavity limiting diaphragmatic descent, particularly when lying in the supine position;29 in addition, thoracic fat weighing on the chest wall can effectively decrease lung compliance, leading to hypoventilation, atelectasis, and ventilation–perfusion mismatch. The reduced lung volumes may decrease airway stiffness by reducing the tracheal tethering effect, further increasing the risk of upper airway collapse during sleep.…”
Section: Obesitymentioning
confidence: 99%
“…Evidence has suggested that, at any level of OSAS severity, the degree of adenotonsillar hypertrophy required to develop OSAS of such magnitude is reduced in obese children [50]. Recent evidence in children has also suggested that OSAS is related to specific areas of fat deposition; more specifically, OSAS severity was shown to be strongly predicted by visceral fat deposition as defined by MRI [51]. Finally, the phenotype of obesity-induced childhood OSAS is markedly different from the OSAS phenotype that is exclusively induced by adenotonsillar hypertrophy [52].…”
Section: Sdb and Obesity: Evidence From Childrenmentioning
confidence: 99%
“…A few prospective studies have looked at only inflammation and overweight/obesity in association with snoring and OSA, but not in-depth the complete spectrum of cardiometabolic biomarkers [20,21]. For instance, OSA in obese children was associated with greater visceral fat area derived using MRI [22]. The same investigators also demonstrated that obese children with OSA (versus obese children without OSA) had higher insulin resistance, triglycerides, and leptin [22], whereas another study showed no changes in leptin among children with versus without OSA [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, OSA in obese children was associated with greater visceral fat area derived using MRI [22]. The same investigators also demonstrated that obese children with OSA (versus obese children without OSA) had higher insulin resistance, triglycerides, and leptin [22], whereas another study showed no changes in leptin among children with versus without OSA [23]. …”
Section: Introductionmentioning
confidence: 99%